Character Planting at Aisyiyah Kindergarten Bustanul Athfal 1 Gedangan During the Covid-19 Pandemic - Anis Khoirunnisa (International Consortium of Education and Culture Research Studies, 2021)
This study aims to identify character education carried out by early mothers during the covid-19 pandemic. This study uses the method of collecting information by conducting interviews with resource persons and seeking relevant funds from news and journals. Cultivating character in children from an early age doubts the efforts to inculcate commendable behavior that begins from childhood. Penumamoun piadis sunk character is influenced by two factors, namely internal factors and external factors kedios, these factors are interconnected in instilling character in children. During the Covid-19 pandemic, the learning process was carried out at a trend, so that the character instilling in children was mostly done in internal factors, regulate the family, so parents can instill character well, then the child will imprint the character well on him, parents have an important role to play. character cultivation because children will have more time with their parents than their teachers, therefore the family environment has a big impact on character building in children.